191k views
5 votes
Find the zeros of the function.

h(x) = (-2x+3) (-x+3)

smaller x: ?
larger x: ?

2 Answers

3 votes

Answer:

smaller x: 1.5

larger x: 3

Explanation:

h(x) = (-2x+3) (-x+3)

Zero of an equation is the x-intercept

-2x+3 = 0

x = 1.5

-x+3 = 0

x = 3

User JFPicard
by
4.5k points
0 votes

Answer:

smaller zero: 3/2

larger zero: 3

Explanation:

h(x) = (-2x+3) (-x+3)

Set equal to zeros to find the zeros

0 = (-2x+3) (-x+3)

-2x +3 =0 -x+3 =0

2x = 3 x = 3

x = 3/2 x = 3

User Chandan Jee
by
5.2k points